IUS CONSTITUENDUM LEGAL STANDING BAGI WNA TERKAIT PROSES JUDICIAL REVIEW DI MAHKAMAH KONSTITUSI DALAM PERSPEKTIF HAK ASASI MANUSIA - prasetio, dicky eko (HUNILA : Jurnal Ilmu Hukum dan Integrasi Peradilan, 2023)
Legal Standing is part of human rights which is related to the permission of certain parties to sue in court. In practice at the Constitutional Court, there is confirmation that legal standing is only given to Indonesian citizens, while foreigners do not get the slightest space to proceed in proceedings at the Constitutional Court. This research aims to analyze future regulatory efforts (ius constituendum) regarding limited legal standing for foreigners in the judicial review process. The term ius constituendum is used in this research to emphasize the existence of legal rules that are being initiated or aspired to be related to granting limited legal standing to foreigners in the judicial review process. This research is normative legal research by prioritizing conceptual, case and statutory approaches. The research results confirm that the modern human rights perspective mandates that the universal application of human rights requires the recognition of human rights for every person without the need to look at the background and national origin of each person. The regulation regarding legal standing at the Constitutional Court problematically only recognizes Indonesian citizens as parties who can have legal standing at the Constitutional Court. Based on the results of legal comparisons with Czechia, Germany and Mongolia, in the future it is necessary to regulate limited legal standing for foreigners to emphasize the existence of universal human rights and aim to protect foreigners from discrimination from countries that do not implement legal policies that accommodate the universalism of  human rights.